Consortium on Methods Evaluating Tobacco: Research Tools to Inform US Food and Drug Administration Regulation of Snus. Issue 11 (4th October 2017) - Berman, Micah L; Bickel, Warren K; Harris, Andrew C; LeSage, Mark G; O'Connor, Richard J; Stepanov, Irina; Shields, Peter G; Hatsukami, Dorothy K
Abstract: Introduction: The US Food and Drug Administration (FDA) has purview over tobacco products. To set policy, the FDA must rely on sound science, yet most existing tobacco research methods have not been designed to specifically inform regulation. The NCI and FDA-funded Consortium on Methods Evaluating Tobacco (COMET) was established to develop and assess valid and reliable methods for tobacco product evaluation. The goal of this article is to describe these assessment methods using a US manufactured "snus" as the test product. Methods: In designing studies that could inform FDA regulation, COMET has taken a multidisciplinary approach that includes experimental animal models and a range of human studies that examine tobacco product appeal, addictiveness, and toxicity. This article integrates COMET's findings over the last 4 years. Results: Consistency in results was observed across the various studies, lending validity to our methods. Studies showed low abuse liability for snus and low levels of consumer demand. Toxicity was less than cigarettes on some biomarkers but higher than medicinal nicotine. Conclusions: Using our study methods and the convergence of results, the snus that we tested as a potential modified risk tobacco product is likely to neither result in substantial public health harm nor benefit. Implications: This review describes methods that were used to assess the appeal, abuse liability, and toxicity of snus. These methods included animal, behavioral economics, consumer perception studies, and clinical trials. Across these varied methods, study results showed low abuse-liability and appeal of the snus product we tested. In several studies, demand for snus was lower than for less toxic nicotine gum. The consistency and convergence of results across a range of multi-disciplinary studies lends validity to our methods and suggests that promotion of snus as a modified risk tobacco products is unlikely to produce substantial public health benefit or harm.